The Question of Landscape. Considering the relationship between cinematography and landscape in Iceland through Maurice Merleau-Ponty's ontology - Gomez Emilsson, I (University of Exeter, 2025)
This thesis aims to consider the relationship between cinematography and landscape through the lens of 20th century French philosopher Maurice Merleau-Ponty’s ontology, using the Icelandic landscape as the topos of the research. My approach mirrors and extends, through the praxis – this is, my practice as a cinematographer – Merleau-Ponty’s reflections on the relationship between vision and world. In a first instance, I lay out a methodology based on Merleau-Ponty’s later and posthumous work, namely Cézanne’s Doubt (1948), Eye and Mind (1964) and The Visible and the Invisible (1964). The methodology aims to link the very technical elements of cinematography to the abstract and conceptual ideas the philosopher developed, which sought to consider the relationship between vision and world, and used artistic practices and technique as critical elements, and landscape as a pars pro toto for the pro-objective nature, what Melreau-Ponty called ‘the Wild Being’. Through, among other interlinking ideas, the philosopher’s seminal notions of ‘the flesh’, ‘the chiasm’ and ‘the invisible’, I consider the encroaching relationship between subject and object and the hidden strata that are implied in the visible, materialized through the means of cinematography. Secondly, I demonstrate the importance of landscape in Icelandic culture, in general and in moving image cultures, through a thorough consideration of literary, fine arts, cinematic and moving image works as well as outlining the specificities of the local landscape and its rendition through cultural outputs. Thirdly, I look at the relationship between cinematography and landscape through the lens of Merleau-Ponty’s ontology in the works of contemporary Icelandic filmmakers, juxtaposing two relevant pieces shot on different formats, comparing and contrasting the use of analogue and digital cinematography in relation to landscape, and unveiling the specificities of the relationship between cinematography and the Icelandic landscape. Finally, I close-read my own practice ...